2014
DOI: 10.1002/macp.201400213
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Chain and Local Mobility of Some Aromatic Polyamides and Their Influence on the Physicochemical Properties

Abstract: This study refers to the relationship between the macromolecular structure of two aromatic fluorinated polyamides and their physical properties, with emphasis on the overall and local chain mobility and their influence upon thermal transitions, dielectric relaxations, and gas permeability/selectivity. One polyamide contains naphthalene and 1,3,4‐oxadiazole units in the main chain, while the other is based on an aromatic asymmetrical diamine containing a phenoxy‐substituted benzophenone segment. Free‐standing, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 65 publications
(88 reference statements)
2
7
0
Order By: Relevance
“…It is possible that some polar molecules (like water) adsorbed during storage are removed from the polyimide films on heating. Similar processes were observed in other aromatic polyimides or polyamides [39,48]. In the second heating cycle, the relative permittivity is no longer decreasing with temperature and the γ relaxation intensity is reduced to some extent.…”
Section: Dielectric Relaxation Behavioursupporting
confidence: 62%
“…It is possible that some polar molecules (like water) adsorbed during storage are removed from the polyimide films on heating. Similar processes were observed in other aromatic polyimides or polyamides [39,48]. In the second heating cycle, the relative permittivity is no longer decreasing with temperature and the γ relaxation intensity is reduced to some extent.…”
Section: Dielectric Relaxation Behavioursupporting
confidence: 62%
“…The polymers could be cast into flexible and tough films from DMA solutions, with T g s between 160 and 220 • C. In addition, 10% mass loss temperatures were recorded in the range of 400 to 505 • C in N 2 and from 380 to 480 • C in air atmosphere. Also, Damaceanu et al [47] prepared two different aromatic fluorinated polyamides. One of the polyamides contained in the main chain 1,3,4-oxadiazole and naphthalene moieties.…”
Section: Polyamides With High Thermal Stability and Flame-retardant Pmentioning
confidence: 99%
“…The values of permeability and selectivity showed well-balanced gas productivity, in particular for the CO 2 /CH 4 separation. Flourinated polyamides, analyzed by Damaceanu et al [ 47 ], showed good permeability properties against different gases, as a function of the structural variations in the polyamide repeating unit.…”
Section: Aromatic Polyamides With Selected Properties and Applicatmentioning
confidence: 99%
“…It is established that mechanical (tensile) properties and stability, which are commonly characterised to evaluate formulated films, are associated with the glass transition temperature (T g ) (Fadda et al, 2010;Connie and John, 2005;Mcphillips et al, 1999). The T g (in addition to the mechanical properties and the physical and chemical stability) of polymer films have, in turn, been related to molecular mobility (Damaceanu et al, 2014;Ballesteros and Walters, 2011;Fadda et al, 2010;Bhugra et al, 2008;Zhang et al, 2013). Characterisation of molecular mobility is therefore important to better understand polymer film performance for pharmaceutical applications.…”
Section: Introductionmentioning
confidence: 98%